“Hopeful feeling[s]:” Utopian Shakespeares and the 2021 Reopening of British Theatres - Hawkins, Rowena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This article focuses on a specific moment in recent British theatre history: the late spring of 2021 when theatres reopened after a prolonged period of closure that had been enforced during the first waves of the Coronavirus pandemic. It considers The HandleBards’ production of Romeo and Juliet (performed at York’s Theatre Royal) and Shakespeare’s Globe Theatre’s production of A Midsummer Night’s Dream in the context of that unusual time. The productions, which both used bright colours and irreverent approaches to create festive atmospheres, had a shared joyful aesthetic which encouraged me to think more deeply about what audiences wanted—and needed—from post-lockdown theatre. In this article, I suggest that these vibrant Shakespeares, when presented in the immediate aftermath of the first waves of Covid, functioned as cathartic utopian performatives. They offered audiences uncomplicated joy and “a hopeful feeling of what the world might be like” after Coronavirus (Dolan 2005, p. 5). They “let audiences experience a processual, momentary feeling of affinity” and encouraged them to “imagine, together, the affective potential of a future in which this rich feeling of warmth, even of love, could be experienced regularly and effectively outside the theatre” (Dolan, p. 14). Utopian performatives are characterised by their transience and, inevitably, the simple joy of these Shakespeares was fleeting. Both venues have since hosted visually and thematically darker productions that have used Shakespeare to explore important social and political issues. Indeed, the HandleBards’ Romeo and Juliet and The Globe’s Midsummer are productions which might, in other circumstances, have been dismissed as simplistic. However, I suggest that these productions offered real hope for the future in the wake of crisis and demonstrate the importance of theatre in challenging times.